2018
DOI: 10.1039/c7an02008b
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution spectral analysis of ammonia near 6.2 μm using a cw EC-QCL coupled with cavity ring-down spectroscopy

Abstract: We report on the development of a mid-infrared cavity ring-down spectrometer (CRDS) coupled with a continuous wave (cw) external cavity quantum cascade laser (EC-QCL), operating between 6.0 μm and 6.3 μm, for high-resolution spectroscopic studies of ammonia (NH3) which served as a bench-mark molecule in this spectral region. We characterized the EC-QCL based CRDS system in detail and achieved a noise-equivalent absorption (NEA) coefficient of 2.11 × 10-9 cm-1 Hz-1/2 for a 100 Hz data acquisition rate. We there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 24 publications
1
9
1
Order By: Relevance
“…In addition to influencing the CH 4 isotopologues, NH 3 had a significant effect on the measured H 2 O concentration, corresponding to 0.41% H 2 O per ppm NH 3 (Figure S1, supporting information). This interference is also apparent in Figure A at the H 2 O absorption lines that are located around 6028.78 cm −1 and is consistent with studies reporting closely related absorption features of NH 3 and H 2 O …”
Section: Resultssupporting
confidence: 91%
“…In addition to influencing the CH 4 isotopologues, NH 3 had a significant effect on the measured H 2 O concentration, corresponding to 0.41% H 2 O per ppm NH 3 (Figure S1, supporting information). This interference is also apparent in Figure A at the H 2 O absorption lines that are located around 6028.78 cm −1 and is consistent with studies reporting closely related absorption features of NH 3 and H 2 O …”
Section: Resultssupporting
confidence: 91%
“…From these analyses we estimate the measurement sensitivity, relative accuracy, and absolute accuracy of our experimental setup for CH 4 and N 2 O detections in the air are around 10-20 pptv, 2, and 20 ppbv. The absolute accuracy could be improved to be comparable to the relative accuracy by calibrating the measurement with standard "known" sample of ppb-level concentration and controlling accurately the laser frequency during the spectral measurements Maithani et al, 2018).…”
Section: Spectralmentioning
confidence: 99%
“…In recent years, with the rapid development of advanced tunable high-power midinfrared sources, especially external-cavity quantum cascade lasers (EC-QCL) (Botez et al, 2018), the LODs of CRDS for trace-gas detections have been greatly improved. For example, Maity et al (2017) achieved an LOD of 52 pptv for CH 4 at 7.5 µm, Banik et al (2017) achieved an LOD of 5 ppbv for N 2 O at 5.2 µm, Long et al (2016) achieved an LOD of 2 pptv for N 2 O at 4.5 µm, Maithani et al (2018) achieved an LOD of 740 pptv for NH 3 at 6.3 µm and Zhou et al (2018) achieved an LOD of 410 pptv for NO at 5.3 µm.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, in this region, water absorbs strongly, making the region less explored. Only Maithani et al reported, in 2018, high resolution and high-sensitive spectroscopic analysis of NH 3 centered at 6.2 µm [18]. Therefore, further work is needed in the wavelength ranges between 5 and 7 µm where strong absorption lines of fundamental and combinational vibrational bands of ν4 and ν2 are located.…”
Section: Introductionmentioning
confidence: 99%